An Assessment of the Application of Generative Artificial Intelligence in News Content Production at Clouds Media Group, Tanzania - Deusdedith M. Kakorozya; Dietrick Kaijanangoma; Camillus Nikata (Technium Social Sciences Journal, 2025)
Purpose: This study assessed the use of generative Artificial Intelligence (AI) in the Clouds Media Group (CMG) newsroom in Tanzania. Applying the Technology Acceptance Model (TAM), it investigated journalists’ attitudes toward the usefulness and ease of use of these tools and their experiential content opportunities, providing a granular view of technology adoption in a Global South context. Methodology: The study adopted a qualitative explanatory design to delve into the nuanced realities of the newsroom. Data was collected through semi-structured, in-depth interviews with six purposefully selected journalists, editors, and technical staff at CMG, ensuring a representation of strategic, operational, and technical perspectives. Thematic analysis, following the framework of Braun and Clarke (2006), was used to analyze the data, generating rich, context-driven insights. Findings: CMG journalists found generative AI beneficial for improving efficiency in research, transcription, and drafting, as well as enhancing creativity in storytelling and data analysis. The tools were widely considered user-friendly, which justified their organic, bottom-up adoption. However, this adoption was hampered by significant challenges, including reliance on informal peer-to-peer training, critically inadequate infrastructure (e.g., poor internet, outdated hardware), and significant ethical issues like the provision of misinformation, inaccuracy, and the potential deskilling of employees. The absence of formal organizational AI policies was a critical gap, leading to piecemeal and uneven assimilation and creating a landscape of both opportunity and risk. Unique Contribution to Theory, Policy, and Practice: The study confirms the primary components of the Technology Acceptance Model (TAM) in the Tanzanian context while simultaneously illustrating a significant "ease of use paradox." This paradox states that while tools may be intrinsically easy to use, their effective adoption is significantly hindered by external structural and training issues, a factor not fully accounted for in the original model. This finding suggests that Technology Adoption Models applied in the Global South need to be re-contextualized to incorporate these critical environmental variables. The report underlines the urgent necessity for drafting national AI ethics guidelines and specific media policies for Tanzania to ensure accountability, transparency, and public trust. Furthermore, it provides media houses with a comprehensive, actionable guide for the responsible incorporation of AI technologies, pivoting on the urgent need for formal training, advanced internal digital infrastructure and internal charters on AI Ethics to govern use.